Dampak Video Breaking Terhadap Peningkatan Keterampilan Mendayung Rowing - Sopyan Rizki Haryadi; Arif Fajar Prasetiyo (BADAN PENERBIT STIEPARI PRESS, 2022)
The research method used in this research is the experimental method. This method is used based on the consideration that the nature of experimental research is trying something to find out the influence or consequences of a treatment or treatment. Apart from that, the author wants to know the effect of the independent variable on the dependent variable that is quoted or observed regarding this experimental method, because in this research we are looking for a cause-and-effect relationship from training using videobreaking to improving rowing skills. By conducting experiments on variables that allow you to get results. This is explained by Lutan, Berliana and Sunaryadi (2007: 146) that: